Mechanical thrombectomy treatment for cerebral infarction in circulation after 40 h - Huang, Yao; Tan, Changya; Xiong, Huifen; Li, Xi; He, Chenyang; Li, Dan; Yang, Jiao; Ran, Xiaohua; Xu, Jing; Fan, Jin (Frontiers in Neurology, 2024)
The treatment time window for acute cerebral infarction in global guidelines is within 24 h. We report a patient who was admitted to the hospital and underwent endovascular treatment reaching 40 h. During vascular examination, the thrombus moved to distant segment, and then the surgeon quickly performed endovascular treatment. The patient ultimately achieved a good outcome. This case indicates that thrombus is moveable at any time, we expected to provide advice to clinical doctors that vascular examination should also be arranged as soon as possible to clarify the etiology in stroke patients especially with low NIHSS scores.